KEMAMPUAN MENENTUKAN FAKTA DAN OPINI SISWA KELAS IX SMP N 3 KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Yuni Chairani; Mangatur Sinaga; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aimed at finding out the ability of deciding fact and opinion by the third grade students at SMP N 3 Kateman Subdistrict of Indragiri Hilir Regency. The samples were 54 students. Descriptive method was used in this research. The subjects were the third grade students of SMP N 3 Kateman Subdistrict of Indragiri Hilir Regency. The data collection was conducted by using a set of test in the form of true – false. The data were analyzed in term of students’ ability in deciding fact and opinion by checking out their worksheets of the test. The findings found that the third grade students at SMP N 3 Kateman Subdistrict of Indragiri Hilir Regency had mediocre ability with the average of 70.55% and low ability with the average of 69.44% in deciding fact and opinion. In brief, the ability of deciding fact and opinion by the third grade students at SMP N 3 Kateman Subdistrict of Indragiri Hilir Regency was mediocre with the average of 70%.Key Words: Reading, Fact and Opinion